HUBUNGAN RIWAYAT KONTAK ANTAR PASANGAN TERHADAP PENULARAN TB PARU KASUS BARU BERDASARKAN HASIL PEMERIKSAAN BTA DI PUSKESMAS PEUREULAK KAB. ACEH TIMUR - BUDI SUBHANA MAULANA IBRAHIM TAMBUNAN; FANI ADE IRMA; SRI REZEKI ARBANINGSIH; RIZKA ARIANI (JURNAL ILMIAH KOHESI, 2021)
The design of this study was cross sectional using the Chi Square test. The number of samples used was 44 respondentswho were positive for pulmonary tuberculosis with BTA +1, +2 and +3 and the results of BTA from the pairs of respondents.The results of the data analysis indicated that there was a relationship between the contact history between husband andwife and the transmission of new cases of pulmonary TB based on the results of the BTA examination at the PeureulakHealth Center, East Aceh Regency. The results of statistical tests using Chi Square showed a value (P = 0.001). Meanwhile,based on the BTA of respondents, it was found that there was no relationship between sex and age on the BTA of therespondents with P-values of 0.986 and 0.250 respectively. Then based on the AFB couples also obtained the results thatthere was no relationship between sex and age on the AFB couples with each P-value of 0.068 and 0.394. Based on theresults of the description above, it can be concluded that there is a relationship between the history of contact betweenhusband and wife partners to the transmission of new cases of pulmonary TB based on the results of the BTA examination atthe Peureulak Health Center, East Aceh Regency.